Dermoscopic analysis of skin changes associated with sun exposure among medical students in a tertiary care center in Central Kerala - Shojan, Tereesa; M, Lakshmipriya; Prathap, Priya; VV, Unnikrishnan (National journal of physiology, pharmacy and pharmacology, 2024)
Background: Skin is an important barrier of the human body, which offers protection from pathogens, UV radiation, and chemical and mechanical injury. Solar UV radiation is the major cause of extrinsic skin aging and it leads to many acute and chronic cutaneous reactions. Dermoscope is an instrument that helps to visualize the morphological features unseen to the naked eye, using the principle of transillumination and magnification of skin. Aim and Objective: The aim of the study was to study the skin changes associated with sun exposure on the lateral and medial aspects of the forearm using dermoscope. Materials and Methods: A cross-sectional descriptive study of 82 1st-year MBBS students belonging to 18–25 years of age was conducted at Government Medical College, Thrissur, after getting ethics committee approval. Sample size calculated was 76. With the help of a questionnaire, personal details and details related to the sun exposure habits of the subjects were obtained. Dermoscopic photographs of the lateral and medial side of the forearm were taken after informed consent. Results: Chi-square test showed significant changes in pigmentation pattern and hair pattern on the lateral side of the forearm among subjects who had sun exposure for more than half an hour which was not found on the medial side. Conclusion: Photoaged skin appears coarse with uneven pigmentation. Dermoscopy allows the assessment of subtle morphological features of skin aging. Monitoring skin changes due to sun exposure among our population helps in the early identification of abnormal patterns with sun exposure which needs immediate medical attention.